2006
DOI: 10.2135/cropsci2006.01.0020
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variation among Canada Wildrye Accessions from Midwest USA Remnant Prairies for Biomass Yield and other Traits

Abstract: Canada wildrye (Elymus canadensis L.) and Virginia wildrye (Elymus virginicus L.), which are native to the USA, were collected from remnant Midwest prairies. The objectives of this study were to determine the genetic variability among the collected accessions for biomass yield and other traits, determine the extent of genotype 3 environment interactions for these traits across Midwest environments, and to determine the relationship between the geographical location of the collection site and evaluation sites f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 19 publications
0
13
0
Order By: Relevance
“…Overlap between some of the CWR and VWR populations is perhaps not surprising. Vogel et al (2006) reported comparable means and ranges for agronomic traits among Midwest populations classified as VWR and CWR. Morphological data, from populations in southern Oklahoma (Nelson and Tyrl, 1978), coupled with additional cytological and allozyme data from Texas populations (Davies, 1977) indicate that gene flow and introgression occurs in the wild between CWR and VWR populations.…”
Section: Resultsmentioning
confidence: 87%
“…Overlap between some of the CWR and VWR populations is perhaps not surprising. Vogel et al (2006) reported comparable means and ranges for agronomic traits among Midwest populations classified as VWR and CWR. Morphological data, from populations in southern Oklahoma (Nelson and Tyrl, 1978), coupled with additional cytological and allozyme data from Texas populations (Davies, 1977) indicate that gene flow and introgression occurs in the wild between CWR and VWR populations.…”
Section: Resultsmentioning
confidence: 87%
“…Accumulated biomass was removed and discarded in October or November of 2004, 2005, and 2006 by cutting plots to a 7-cm height. Plots were harvested and data collected on plant survival and size in June 2007.…”
Section: Methodsmentioning
confidence: 99%
“…It was concluded that Virginia wildrye would be better suited for conservation plantings than for forage when used in the northeastern United States. Research in the midwestern United States indicated that Virginia wildrye was less productive than Canada wildrye (Elymus canadensis L.; Vogel et al, 2006). Programs such as CREP have created a need for more information on the suitability of locally adapted native grasses for the northeastern United States.…”
Section: Virginia Wildrye Persistence and Performance In Riparian Areasmentioning
confidence: 99%
“…Prior to the release of the cultivar Homestead, only one cultivar each of Canada wildrye and Virginia wildrye had been released or developed. ‘Mandan’ Canada wildrye was developed from collections made near Mandan, ND (Alderson and Sharp 1994), and it is not well adapted to the Central Great Plains and Midwest, USA (Vogel et al, 2006). Omaha wildrye is a privately developed Virginia wildrye cultivar that is produced by Stock Seed Farms, Murdock, NE.…”
mentioning
confidence: 99%